PENGARUH STRATEGI DIFERENSIASI TERHADAP KEUNGGULAN BERSAING (STUDI PADA HOTEL RESTY MENARA PEKANBARU) - Ratna Paryanti; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted at the Resty Tower Hotel Pekanbaru, this research aims to determine the effect on competitive advantage differentiation strategy. Differentiation strategy as an independent variable (X). While the competitive advantage as the dependent variable (Y).The research sample of one hundred (100) respondents from the population by using the formula slovin. Data obtained from the questionnaire and subsequently processed to then be tested with the help of statistics through SPSS pragram. Results of calculation of the coefficient of determination is 0.534. That is, differentiation strategies affecting competitive advantage of 53.4%.Keywords: Differentiation Strategy, Competitive Advantage, Resty Menara Hotel.